Protective effects of antihypertensive treatment in patients aged 85 years or older. Issue 7 (July 2017) - Corrao, Giovanni; Rea, Federico; Monzio Compagnoni, Matteo; Merlino, Luca; Mancia, Giuseppe
Abstract : Objective: To assess whether in individuals aged 85 years or older, adherence to antihypertensive drugs is accompanied by a reduced risk of cardiovascular events. Methods: A nested case–control study was carried out on a cohort of patients aged 85 years or older, who were newly treated with antihypertensive drugs between 2007 and 2009, using the database available for all citizens (about 10 million) of Lombardy (Italy). Cases were the cohort members who experienced death or hospital discharge for stroke, myocardial infarction (MI) or heart failure from the initial prescription until 2012. Up to five controls were randomly selected for each case. Logistic regression was used to model the outcome risk associated with the adherence with antihypertensive drug therapy. A patient cohort aged 70–84 years was taken for comparison. Results: Compared with patients with very low adherence, those aged 85 years or older (average 88 years) with high adherence showed a risk reduction for death (47%; 95% confidence interval, 5–57%) and all the outcomes combined (34%; 95% confidence interval, 21–45%). The risk of heart failure and stroke was also reduced, whereas the risk of MI was not affected by adherence with antihypertensive drugs. Similar findings were obtained in the cohort of patients aged 70–84 years. Conclusion: Adherence with antihypertensive drug therapy reduced the risk of cardiovascular morbidity in patients aged 85 years or more, the benefit including heart failure and stroke, although not MI, and extending to all-cause death.